Basic principles of nanotechnology - Sanders, Wesley Crowell; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
The book allows the reader to have a basic understanding of the structure and properties of nanoscale materials routinely used in nanotechnology-based research and industries. To add, the book describes the operation of nanoscale transistors and the processes used to fabricate the devices. Additionally, it presents research involving the use of carbon nanotubes, graphene, and molecules to create non-silicon based electronic devices. It aims to provide an understanding of the operation of the most frequently used fabrication and characterization procedures, such as scanning electron microscopy, atomic force microscopy, etch, e-beam lithography, and photolithography.
chapter 1 Introduction to Nanotechnology -- chapter 2 Chemistry Foundations in Nanotechnology -- chapter 3 Physics Foundations in Nanotechnology -- chapter 4 Allotropic Carbon-Based Nanomaterials -- chapter 5 Molecule-Based Nanotechnology -- chapter 6 Inorganic Nanomaterials -- chapter 7 Nanoscale Characterization -- chapter 8 Nanofabrication Techniques.
Keywords: TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; Nanotechnology; SCIENCE / Physics; TECHNOLOGY & ENGINEERING / Nanotechnology & MEMS